2021
DOI: 10.1002/lno.11948
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophy upgrades food quality for marine calanoid copepods

Abstract: Inorganic nutrient limitation affects the stoichiometry and nutritional quality of marine phytoplankton. Mixoplankton, able to photosynthesize and feed simultaneously in the one cell, can compensate shortage of nutrients by phagotrophy, theoretically upgrading their nutritional quality for their predators: the zooplankton. Yet, the additional value that phagotrophy in mixoplankton may provide to support zooplankton growth and recruitment has been poorly explored. Therefore, we investigated the feeding and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
(107 reference statements)
2
10
0
Order By: Relevance
“…Scanty information is available about the feeding preferences of this copepod, but C. typicus is generally described as an omnivorous species with mixed feeding strategy privileging herbivory (Benedetti et al, 2016(Benedetti et al, , 2018. The fact that in our 20-year study egg production was inversely correlated to phytoplankton concentration (total, diatoms, and phtyoflagellates), and that peaks in egg production always anticipated phytoplankton abundance, seems to confirm that C. typicus may preferentially feed on non-authotrophic and/or mixotrophic food items (ciliates and dinoflagellates) (Broglio et al, 2004;Traboni et al, 2021), and that microzooplankton diets can promote higher fecundity and/or hatching success in this species (Bonnet & Carlotti, 2001). Recently, it was demonstrated that mixotrophic-related improvement of food quality in protists increased C. typicus EPR and naupliar recruitment (Traboni et al, 2021), thus suggesting that this feeding strategy may help this species to overcome unfavorable food environments.…”
Section: Relationships Among Reproductive Traits Abundances and Envir...supporting
confidence: 66%
“…Scanty information is available about the feeding preferences of this copepod, but C. typicus is generally described as an omnivorous species with mixed feeding strategy privileging herbivory (Benedetti et al, 2016(Benedetti et al, , 2018. The fact that in our 20-year study egg production was inversely correlated to phytoplankton concentration (total, diatoms, and phtyoflagellates), and that peaks in egg production always anticipated phytoplankton abundance, seems to confirm that C. typicus may preferentially feed on non-authotrophic and/or mixotrophic food items (ciliates and dinoflagellates) (Broglio et al, 2004;Traboni et al, 2021), and that microzooplankton diets can promote higher fecundity and/or hatching success in this species (Bonnet & Carlotti, 2001). Recently, it was demonstrated that mixotrophic-related improvement of food quality in protists increased C. typicus EPR and naupliar recruitment (Traboni et al, 2021), thus suggesting that this feeding strategy may help this species to overcome unfavorable food environments.…”
Section: Relationships Among Reproductive Traits Abundances and Envir...supporting
confidence: 66%
“…This rule applies to all marine organisms, including protistan grazers, such as microzooplankton (pure heterotrophic protists) and mixoplankton (autotrophic protists with phagotrophic capability). Both groups of protistan grazers, which encompass many ciliates and dinoflagellates, are key components of marine pelagic food webs because of their functions as major grazers of phytoplanktonic primary production and as very important prey for larger zooplankton ( Calbet, 2001 ; Calbet and Saiz, 2005 ; Flynn et al, 2019 ; Traboni et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that phytoplankton exhibit wide variations in their elemental composition and protozoans are more homoeostatic, showing a narrower range of variation ( Sterner and Elser, 2002 ; Klausmeier et al, 2004 ). However, several studies have shown that the elemental stoichiometry of protozoans may vary significantly in response to the environment and prey composition ( Hantzsche and Boersma, 2010 ; Malzahn et al, 2010 ; Meunier et al, 2012 ), and may affect the energy transfer to upper trophic levels ( Traboni et al, 2021 ). The incorporation of elemental ratios and absolute elemental contents (dependent on cellular volume) of different planktonic groups into ecosystem models could improve our ability to predict the response of planktonic communities to environmental threats, and help to understand their influence on the biogeochemistry of the ocean ( Litchman et al, 2013 ; Meunier et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As this result was observed in both absolute and relative abundances, this suggests that phytoplankton had much higher growth rates than mixoplankton, and/or that the grazing pressure by mesozooplankton, Calanus spp. in this region (Head et al, 2000), was more intense on mixoplankton as they can have better nutritional quality (Traboni et al, 2021). Indeed, we saw that this timing also corresponded with a number of different shifts, including a loss in relative protistan motility, which is often a trait associated with the flagellates that perform mixotrophy, as well as a decline in nutrients and an increase in bacterial production (Figures S6, S7).…”
Section: Discussionmentioning
confidence: 72%